2020
DOI: 10.1111/ddi.13065
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structural complexity explains patterns of feral cat and dingo occurrence in monsoonal Australia

Abstract: AimAn interaction between reduced habitat structural complexity and predation by feral cats (Felis catus) has been hypothesized as the primary driver of mammal decline in northern Australia. However, we have a limited understanding of the drivers of the distribution and abundance of feral cats at a landscape scale, including whether the occurrence of a top predator, the dingo (Canis familiaris [dingo]), limits feral cat populations. We modelled feral cat and dingo site occurrence, to provide the first broad‐sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 58 publications
7
42
1
Order By: Relevance
“…In this special issue, Davies et al (2020) extend the generality of these observations yet further, by showing that the abundance of feral cats on Melville Island, Northern Territory, is positively related to increased disturbance from high frequencies of intense fire and heavy grazing by feral stock. This corroborates another recent study from northern Australia that found that feral cats were less likely to be present in productive habitats unless those habitats experienced high fire activity (Stobo-Wilson et al 2020a).…”
Section: Cat Ecology and Impactssupporting
confidence: 91%
“…In this special issue, Davies et al (2020) extend the generality of these observations yet further, by showing that the abundance of feral cats on Melville Island, Northern Territory, is positively related to increased disturbance from high frequencies of intense fire and heavy grazing by feral stock. This corroborates another recent study from northern Australia that found that feral cats were less likely to be present in productive habitats unless those habitats experienced high fire activity (Stobo-Wilson et al 2020a).…”
Section: Cat Ecology and Impactssupporting
confidence: 91%
“…Unfortunately, we do not have ground-based data with which to compare the density of understorey vegetation across our four grids. However, a remote-sensed measured response of habitat productivity, that correlates with the density of green vegetation (Pickett-Heaps et al 2014;Stobo-Wilson et al 2020), does not support this. Instead, it suggests that the average vegetation density across the Ranku grid is more comparable with that of the Pickertaramoor grid, while the vegetation density at Cache Point is comparable to that of the Cape Fourcroy grid (H. Davies, unpubl.…”
Section: Discussionmentioning
confidence: 97%
“…In northern Australian savannas, feral cat site-occupancy is higher in areas with lower understorey vegetation density (Stobo-Wilson et al 2020). As such, productivity-driven variation in vegetation density across the islands could have contributed to the observed variation in cat density.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations